Influencia de los laboratorios de computación como recurso didáctico en el proceso de enseñanza - aprendizaje en la Escuela Fiscal mixta Paúl Harris de la ciudad de Machala periodo lectivo 2012-2013. - Jiménez Castillo, Viviana Anabel (2013)
The elements of the teaching-learning process, the technological resources such as the computer lab, its classification, its infrastructure will help to have a clear idea of ​​what we want to investigate, ending with the investigation.